2014
DOI: 10.1128/jvi.01679-14
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A Virus Acquires Enhanced Pathogenicity and Transmissibility after Serial Passages in Swine

Abstract: Genetic and phylogenetic analyses suggest that the pandemic H1N1/2009 virus was derived from well-established swine influenza lineages; however, there is no convincing evidence that the pandemic virus was generated from a direct precursor in pigs. Furthermore, the evolutionary dynamics of influenza virus in pigs have not been well documented. Here, we subjected a recombinant virus (rH1N1) with the same constellation makeup as the pandemic H1N1/2009 virus to nine serial passages in pigs. The severity of infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…It is also possible that the virus gained host adaptations upon transmission that could have facilitated more efficient replication. Phenotypic changes in influenza viruses due to adaptation to the host have been shown in IAV studies in feral swine, domestic swine, and mice and have also been demonstrated for IDV in the guinea pig transmission model (11)(12)(13)(14). Future studies will characterize the pathogenesis in the contact calves and potentially identify mutations in the isolates recovered from the contact calves.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the virus gained host adaptations upon transmission that could have facilitated more efficient replication. Phenotypic changes in influenza viruses due to adaptation to the host have been shown in IAV studies in feral swine, domestic swine, and mice and have also been demonstrated for IDV in the guinea pig transmission model (11)(12)(13)(14). Future studies will characterize the pathogenesis in the contact calves and potentially identify mutations in the isolates recovered from the contact calves.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple IAV subtypes can co-circulate in swine herds and persist at the population level for prolonged periods of time (Corzo et al, 2013;Diaz et al, 2015). Additionally, multiple alleles (sequence variants of the same virus) can coexist during IAV infection of pigs (Murcia et al, 2012), and the same virus can evolve differently in the upper and lower respiratory tract of pigs (Wei et al, 2014). Furthermore, nucleotide substitutions within the HA antigenic sites can occur shortly after infection of pigs with no significant differences noticed between pigs with or without immunity to the virus (Diaz et al, 2013;Murcia et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously shown that IAV reassortants having genetic exchange of regulatory genes such as NS, or replication machinery such as PA and PB2, can alter the viral kinetics and immune modulatory phenotype of IAVs (26)(27)(28)(29)(30). Thus, replication kinetics were evaluated for reassortants having genetic exchange between structural and nonstructural genes among the parental viruses, swH1N2 and huH1N1.…”
Section: Resultsmentioning
confidence: 99%
“…The polymerases from the 1957, 1968, and 2009 pandemics were derived from reassortants (5). Protein components of the RNP complex have been implicated in various aspects of influenza virus virulence and pathogenicity in a variety of mammalian models, including mice, ferrets, and swine (25)(26)(27)(28)(29). For example, the well-described amino acid K627 in the PB2 protein enhances polymerase activity, leading to increased transmission, replication, and pathogenicity in mammals (30).…”
mentioning
confidence: 99%